Privacy Of The Termination Of The Agrucultural Concession Contract Within The Law 10- 03. - SAHI, Belgacem; BOUAMRANE, Adel (University of Eloued جامعة الوادي, 2020)
The law No 10/03 of 15 August 2010, defining the terms and conditions of the exploitation of agricultural lands belonging to the private property of the state, has conferred on the Administration of national properties the power to unilaterally, terminate the agricultural concession contract; this power is normally reserved to the judiciary, in accordance with a specific procedure to be observed, in the event of a breach by the concessionary of one or more of the contractual obligations, stipulated in the technical specifications book, annexed to the Executive Decree nr. 10/326 of 23 December 2010. On the other hand, the concessionaire has been granted the right to go to court to seek the annulment of the termination of the concession contract or to call into question the amount of the compensation resulting from this termination. منح القانون رقم 10/03 المؤرخ في 15 أوت 2010 المحدد لشروط وكيفيات استغلال الأراضي الفلاحية التابعة للأملاك الخاصة للدولة، استثناء لإدارة الأملاك الوطنية سلطة الفسخ الإداري لعقد الامتياز الفلاحي والتي تعد في الأصل من صميم اختصاص القضاء وفق إجراءات معينة من الواجب مراعاتها في حالة إخلال المستثمر صاحب الامتياز بالتزام أو أكثر من التزاماته التعاقدية المنصوص عليها في دفتر الشروط الملحق بالمرسوم التنفيذي رقم: 10/326، المؤرخ في: 23 ديسمبر 2010 المحدد لكيفيات تطبيق حق الامتياز لاستغلال الأراضي الفلاحية التابعة للأملاك الخاصة للدولة، وبالمقابل منح للمستثمر صاحب الامتياز الحق في اللجوء إلى القضاء للطعن في قرار فسخ عقد الامتياز أو في مبلغ التعويض المترتب عن هذا الفسخ.
مجلد11، عدد3
Keywords: Agricultural Concession Contract; Unilaterally; Administration of National Properties; Concessionary; Contractual Obligations; Judicial Appeal.; عقد الامتياز الفلاحي؛ الفسخ؛ إدارة أملاك الدولة؛ صاحب الامتياز؛ الالتزامات التعاقدية؛الطعن القضائي